Evaluation and Treatment Results of Ovarian Cysts in Childhood and Adolescence: A Multicenter, Retrospective Study of 100 Patients - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ELSEVIER SCIENCE INC, 2017)
Study Objective: To investigate the characteristics of children with ovarian cysts and evaluate treatment strategies. Design: Retrospective study. Setting: Eight pediatric endocrinology clinics, Turkey. Participants: A total of 100 children and adolescents with ovarian cysts. Interventions: Patient data collected via retrospective chart review. Patients were stratified according to age into 4 groups (newborns, 1-12 months, 1-8 years, and 8-18 years). Main Outcome Measures: Special emphasis was given to torsion and tumor cases, concomitant diseases, treatment modalities, and problems during follow-up. Results: Most newborns and infants were asymptomatic with the cysts being discovered incidentally; in girls ages 1-8, symptoms were common, including breast budding (47.1%, 16 of 34) and vaginal bleeding (29.4%, 10 of 34). Girls older than 8 years mostly presented with abdominal pain (31.6%, 12 of 38) and menstrual irregularity (21.1%, 8 of 38). Most of our patients were diagnosed with a simple ovarian cyst, but 9 patients were found to have ovarian tumors. Ovarian torsion was detected in 7 patients; 5 with large and 2 with small cysts (! 20 mm). Two patients had central precocious puberty (CPP) at presentation and 5 patients developed CPP during follow-up. The surgical intervention rate was high (38%, 38 of 100), but was associated with earlier treatment year, and this association remained significant after adjusting for confounders (P = .035). Conclusion: Most girls have simple cysts, which have a favorable prognosis without intervention; however, there might be coexisting pathologies or complications such as tumors, torsion, and CPP; hence these patients should be evaluated accordingly and treated with a multidisciplinary approach.
Keywords: Ovarian cyst; Ovarian tumor; Ovarian torsion; Precocious puberty; Aromatase inhibitors; CONGENITAL ADRENAL-HYPERPLASIA; MCCUNE-ALBRIGHT SYNDROME; STIMULATORY G-PROTEIN; PRECOCIOUS PUBERTY; 21-HYDROXYLASE DEFICIENCY; ACTIVATING MUTATIONS; CHILDREN; MANAGEMENT; NEONATE; TORSION